Narrative “twist” shifts within-individual neural representations of dissociable story features - Clara Sava-Segal; Clare Grall; Emily S. Finn (Proceedings of the National Academy of Sciences, 2026)
Given the same input, understanding of that input can differ depending on context. How does the brain represent the latent mental frameworks that support different interpretations of the same sensory information? In this study, participants listened to the same auditory narrative twice; the narrative had a plot twist in the middle that dramatically shifted interpretations of the story. Using a within-subject design that held both the stimulus and the individual constant, we leveraged reinterpretation-driven shifts in neural activity between the two listens to identify where representations of different narrative elements are updated under a new interpretative framework. We separated the narrative into three interrelated levels—the overall narrative model, episodes, and characters—to determine where reinterpretation-driven updates to each element were reflected in brain activity. Neural activity patterns associated with interpretations and reinterpretations of these three elements were observed in overlapping but partially distinct sets of temporal, parietal, and prefrontal regions. Results suggest that heteromodal cortex represents specific narrative elements according not to their surface features, but to latent conceptual frameworks for understanding those elements, which can shift under a new narrative interpretation.